Financial Performance Analysis on Micro, Small, and Medium Enterprises of Cassava Product in Cibadak, Lebak Regency, - Denis Mukarromah; Jubaedah Jubaedah; Miguna Astuti (Jurnal Economia, 2020)
Abstract: There are indications of difficult capital access for MSMEs in Lebak. It is shown by Statistic Bureau (BPS) data in Banten Province that only 7.44% of micro and small businesses in Banten obtain or apply for credit, or only 0.95% of Lebak micro and small businesses that can obtain or apply for credit. This research aims to determine the effect of (1) financial literacy on financial performance and (2) financial management on financial performance. This research is quantitative descriptive. The subjects were MSMEs of cassava processed products in Cibadak, Lebak Regency by distributing questionnaire to 86 samples. The data analysis technique used was descriptive analysis and inferential analysis with Partial Least Square (PLS). The results of this research show that (1) financial literacy has a positive effect on financial performance, and (2) financial management has a positive effect on financial performance.Keywords: financial literacy, financial management, financial performance Analisis Kinerja Keuangan pada Pelaku UMKM Produk Olahan Singkong di Cibadak Kabupaten Lebak, BantenAbstrak: Terdapat indikasi sulitnya akses permodalan pada UMKM di Lebak, Banten. Ditunjukan oleh data BPS Provinsi Banten bahwa hanya 7,44% usaha mikro dan kecil di Banten yang memperoleh ataupun mengajukan kredit atau hanya 0,95% dari usaha mikro dan kecil Lebak yang dapat memperoleh atau mengajukan kredit. Penelitian ini bertujuan untuk mengetahui pengaruh (1) literasi keuangan terhadap kinerja keuangan, (2) pengelolaan keuangan terhadap kinerja keuangan. Bentuk penelitian ini adalah deskriptif kuantitatif. Subjek dalam penelitian ini adalah pelaku UMKM produk olahan Singkong di Cibadak, Kabupaten Lebak dengan penyebaran kuisioner pada 86 sampel. Teknik analisis data yang digunakan adalah analisis deskriptif dan analisis inferensial dengan Partial Least Square (PLS). Hasil penelitian ini menunjukan (1) literasi keuangan berpengaruh positif terhadap kinerja keuangan, dan (2) pengelolaan keuangan berpengaruh positif terhadap kinerja keuangan.Kata kunci: literasi keuangan, pengelolaan keuangan, kinerja keuangan